O Modelo de Gestão da Toyota: uma análise do Lean Manufacturing ou Manufatura Enxuta baseada na Teoria Marxiana do Valor Trabalho - Almeida, Lucas Milanez de Lima (2010)
This paper makes a theoretical analysis of management techniques more efficient and widespread, called the Toyota Production System (TPS). As guide, we use the economic theory of labor value developed by Marx in The Capital. In order to understand the TPS, the study was conducted in books, articles, technical manuals and specialized sites. The research accomplished has shown that the TPS arose from the need to adapt the American model of mass production to the current reality faced by global capitalism, in general, and in particular by Japan. We also saw that the essence of lean manufacturing is to reduce the period of turn-over of capital, in that it seeks a lower lead time of production and a rise product quality, through the maximum coincidence of the time of production and the working period and of the elimination of the time of circulation. Moreover, it was light the origin of production flexibility achieved by the lean manufacturing. Finally, the conclusion we have reached is that the Marxist labor value theory is able to give a scientific explanation for the why of a capitalist adapt to the Toyota Production System.